Requirements and expectations of high‐quality biomarkers for atopic dermatitis and psoriasis in 2021—a two‐round Delphi survey among international experts. (17th May 2022) - Ziehfreund, S.; Tizek, L.; Hangel, N.; Fritzsche, M.‐C.; Weidinger, S.; Smith, C.; Bryce, P.J.; Greco, D.; van den Bogaard, E.H.; Flohr, C.; Rastrick (UCB), J.; Eyerich, S.; et al.
Abstract: Background: Chronic inflammatory skin diseases such as atopic dermatitis (AD) and psoriasis (PSO) present major challenges in health care. Thus, biomarkers to identify disease trajectories and response to treatments to improve the lives of affected individuals warrant great research consideration. The requirements that these biomarkers must fulfil for use as practical clinical tools have not yet been adequately investigated. Aim: To identify the core elements of high‐quality AD and PSO biomarkers to prepare recommendations for current biomarker research. Method: A cross‐sectional two‐round Delphi survey was conducted from August to October 2019 and October to November 2020. All participants were members of the BIOMAP project, an EU‐funded consortium of clinicians, researchers, patient organizations and pharmaceutical industry partners. The first round consisted of three open‐ended questions. Responses were qualitatively analysed, and 26 closed statements were developed. For the second round, 'agreement' was assumed when the responses of ≥70% of the participants were ≥5 points on a 7‐point Likert scale for each statement. Priority classification was based on mean scores (<20th percentile = low, 20th to 60th percentile = medium, >60th percentile = high). Results: Twenty‐one and twenty‐six individuals participated in rounds one and two, respectively. From 26 statements that were included in round 2, 18 achieved agreement (8 concerning the performance, 8 for the purpose and 2 on current obstacles). Seven statements were classified as high priority, e.g. those concerning reliability, clinical validity, a high positive predictive value, prediction of the therapeutic response and disease progression. Another seven statements were assigned medium priority, e.g. those about analytical validity, prediction of comorbidities and therapeutic algorithm. Low priority included four statements, like those concerning cost effectiveness and prediction of disease flares. Conclusion: The core requirements that experts agreed on being essential for high‐quality AD and PSO biomarkers require rapid validation. Biomarkers can therefore be assessed based on these prioritized requirements.